Validity of verbal autopsy method to determine causes of death among adults in the urban setting of Ethiopia - Misganaw, Awoke (BioMed Central, 2012)
BACKGROUND: Verbal autopsy has been widely used to estimate causes of death in settings with inadequate vital registries, but little is known about its validity. This analysis was part of Addis Ababa Mortality Surveillance Program to examine the validity of verbal autopsy for determining causes of death compared with hospital medical records among adults in the urban setting of Ethiopia. METHODS: This validation study consisted of comparison of verbal autopsy final diagnosis with hospital diagnosis taken as a “gold standard”. In public and private hospitals of Addis Ababa, 20,152 adult deaths (15 years and above) were recorded between 2007 and 2010. With the same period, a verbal autopsy was conducted for 4,776 adult deaths of which, 1,356 were deceased in any of Addis Ababa hospitals. Then, verbal autopsy and hospital data sets were merged using the variables; full name of the deceased, sex, address, age, place and date of death. We calculated sensitivity, specificity and positive predictive values with 95% confidence interval. RESULTS: After merging, a total of 335 adult deaths were captured. For communicable diseases, the values of sensitivity, specificity and positive predictive values of verbal autopsy diagnosis were 79%, 78% and 68% respectively. For non-communicable diseases, sensitivity of the verbal autopsy diagnoses was 69%, specificity 78% and positive predictive value 79%. Regarding injury, sensitivity of the verbal autopsy diagnoses was 70%, specificity 98% and positive predictive value 83%. Higher sensitivity was achieved for HIV/AIDS and tuberculosis, but lower specificity with relatively more false positives. CONCLUSION: These findings may indicate the potential of verbal autopsy to provide cost-effective information to guide policy on communicable and non communicable diseases double burden among adults in Ethiopia. Thus, a well structured verbal autopsy method, followed by qualified physician reviews could be capable of providing reasonable cause specific mortality estimates in Ethiopia. However, the limited generalizability of this study due to the fact that matched verbal autopsy deaths were all in-hospital deaths in an urban center, thus results may not be generalizable to rural home deaths. Such application and refinement of existing verbal autopsy methods holds out the possibility of obtaining replicable, sustainable and internationally comparable mortality statistics of known quality. Similar validation studies need to be undertaken considering the limitation of medical records as “gold standard” since records may not be confirmed using laboratory investigations or medical technologies. The validation studies need to address child and maternal causes of death and possibly all underlying causes of death.